Empowering public administrators : ethics and public service values - Olejarski, Amanda M., 1982-; Neal, Sue M. (New York, NY : Routledge, 2024)
"Public administrators need to be empowered to make difficult decisions. Acting in the public interest often means doing what is ethical even when it is the unpopular choice. Yet too often, public servants at the local, state, and federal levels internalize the notion that their hands are tied and that they are limited in their ability to effect change. Empowering Public Administrators: Ethics and Public Service Values provides a much-needed antidote to inaction, offering a new lens for viewing administrative decision-making and behavior. This book makes a case for bringing historically significant theories to the forefront of public service ethics by applying them to a series of current ethical challenges in practice. Exploring administrative discretion as modern bureaucrats govern public affairs in a political context, this collection builds on the normative foundations of public administration and provides readers with a scaffold for understanding and practicing public service values. Questions for discussion and applications to practice are included in each chapter making this collection of interest to public affairs masters and doctoral students as well as public service practitioners"--
Introduction / Amanda M. Olejarski & Sue M. Neal -- Ethics and public service values : ontological and epistemic frameworks for study and practice / Sharon H. Mastracci & Norma M. Riccucci -- Autonomy as public service / Beverly Harkema -- Call the budget police! : how the public service values of ontology and epistemology can support public administrators in a gray budgeting environment / Ratna Okhai & Terry N. Henley -- The ethical voids of the principal agency and stewardship approach / Rik Koolma -- How public administrators empower themselves / David S. Reed -- Political polarization, transcendent values, and the urgency of moral leadership among campus leaders as public administrators / Lynn Pasquerella -- The ethics of public employee disparaging private social media use, erosion of trust and the advancement of the public interest / Marcus D. Mauldin -- Principle organizational dissent and public service / Robert Roberts -- The influence of public service values on implementation and performance : evidence from the housing policy / Melissa Gomez Hernandez -- The institutionalization of ethics policies and the management of a growing ethics bureaucracy / Christopher Demmke -- Balancing politics and administration : dangers of administrative discretion / Steven G. Koven -- Ethical codes, the politics-administration dichotomy, and public financial managers / Vickie Edwards & Vincent Reitano -- Discretionary ethics and governing public affairs in jails and prisons : upholding constitutional rights to health and safety / Cynthia Golembeski, Gabriel Eber, Carolyn Sufrin, Jacqueline Lantsman, Homer Venters -- Mending the fragile credibility of a hollow state with storytelling / Jourdan A. Davis -- Gaming the system : ethical constraints in implementing co-production / Meril Antony -- Sports as mirrors : athletes and agenda setting in a hollowed-out state / Jamie Levine Daniel & M. Blair Thomas -- Public service values and financial reporting in U.S. local governments : reconciling transparency in external financial reporting with political expectations / Jane Beckett-Camarata -- Transparency in preserving and administering sites of collective memory / Daniel Boden -- New public management reforms, ethics training programs and ethical conduct of public servants in Tanzania / Wilfred Lameck -- Conclusion / Amanda M. Olejarski & Sue M. Neal.
Keywords: Public administration -- Moral and ethical aspects; Public officers -- Professional ethics; Civil service ethics; Administrative responsibility; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Government / General